Comparative Study of Stability Constant Values of As(III) Complexes with Amino Acids - Kajala, Anita; Sharma, Jitender; Gupta, O.D. (Asian Journal of Chemistry, 2010)
The study of reduction of As(III) with amino acids (L-valine, isoleueine) has been investigated electrochemically in aqueous medium at d.m.e. The stability constants of As(III) with L-valine and isoleucine have been investigated polarographically at 304 and 314 K in aqueous medium. The complexes of As(III) with these ligands ratio as 1:1, 1:2, 1:3 have been reported. DeFord and Hume's method is used to calculate the stepwise formation constants. The mathematical Mihailov's method was also used. The reduction of the system in each case is quasi-reversible and diffusion controlled involving three electrons. The constant ionic strength (μ = 1 M) has been maintained using KNO3 as a supporting electrolyte. Gellings method was used to calculate Er1/2 values for As(III) complexes. The thermodynamic functions (DG°, DH° and DS°) have been calculated to understand the temperature effect on the stability of the complexes.